Interaction between glycolipid MPIase and proteinaceous factors during protein integration into the cytoplasmic membrane of E. coli - Nishikawa, Hanako; Sawasato, Katsuhiro; Mori, Shoko; Fujikawa, Kohki; Nomura, Kaoru; Shimamoto, Keiko; Nishiyama, Ken-Ichi (Frontiers in Molecular Biosciences, 2022)
Protein integration into biomembranes is an essential biological phenomenon common to all organisms. While various factors involved in protein integration, such as SRP, SecYEG and YidC, are proteinaceous, we identified a glycolipid named MPIase (Membrane Protein Integrase), which is present in the cytoplasmic membrane of E. coli. In vitro experiments using inverted membrane vesicles prepared from MPIase-depleted strains, and liposomes containing MPIase showed that MPIase is required for insertion of a subset of membrane proteins, which has been thought to be SecYEG-independent and YidC-dependent. Also, SecYEG-dependent substrate membrane proteins require MPIase in addition. Furthermore, MPIase is also essential for insertion of proteins with multiple negative charges, which requires both YidC and the proton motive force (PMF). MPIase directly interacts with SecYEG and YidC on the membrane. MPIase not only cooperates with these factors but also has a molecular chaperone-like function specific to the substrate membrane proteins through direct interaction with the glycan chain. Thus, MPIase catalyzes membrane insertion by accepting nascent membrane proteins on the membrane through its chaperone-like function, i.e., direct interaction with the substrate proteins, and then MPIase functionally interacts with SecYEG and YidC for substrate delivery, and acts with PMF to facilitate and complete membrane insertion when necessary. In this review, we will outline the mechanisms underlying membrane insertion catalyzed by MPIase, which cooperates with proteinaceous factors and PMF.